2022
DOI: 10.1515/ntrev-2022-0478
|View full text |Cite
|
Sign up to set email alerts
|

Layered double hydroxides (LDHs) modified cement-based materials: A systematic review

Abstract: Ion erosion and carbonization in concrete are the key factors leading to the deterioration of durability. Layered double hydroxides (LDHs) are a kind of functional material with layered structures and ion exchange properties, which can capture a variety of harmful anions in concrete pore solutions. Therefore, LDHs exhibit great potential in improving the durability of concrete as new modified material. This article reviews the recent progress of LDHs. Based on the structural characteristics of LDHs, this work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 113 publications
0
0
0
Order By: Relevance
“…In the area of corrosion assessment using simulated concrete pores (SCP), there is no systematic literature review that follows or adapts the PRISMA methodology, the only systematic review found is related to the use of cement-based materials modified with double hydroxides in layers (LDHs) (ZHAI et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In the area of corrosion assessment using simulated concrete pores (SCP), there is no systematic literature review that follows or adapts the PRISMA methodology, the only systematic review found is related to the use of cement-based materials modified with double hydroxides in layers (LDHs) (ZHAI et al, 2022).…”
Section: Methodsmentioning
confidence: 99%